High Vulnerability of Coastal Wetlands in Chile at Multiple Scales Derived from Climate Change, Urbanization, and Exotic Forest Plantations - Alaniz-Baeza, A; Carvajal-Leon, M; Hidalgo-Corrotea, C (Elsevier B.V., 2023)
Coastal wetlands are considered one of the most vulnerable ecosystems worldwide; the ecosystem services they provide and the conservation of their biodiversity are threatened. Despite the high ecological and socioenvironmental value of coastal wetlands, regional and national vulnerability assessments are scarce. In this study we aimed to assess the vulnerability of coastal wetlands in Chile from 18°S to 42°S (n = 757) under a multiscale approach that included drivers associated with climate change and land cover change. We assessed multiple drivers of vulnerability at three spatial scales (10 m, 100 m, and 500 m) by analyzing multiple remote sensing data (16 variables) on land cover change, wildfires, climatic variables, vegetation functional properties, water surface and importance for biodiversity. We constructed a multifactorial vulnerability index based on the variables analyzed, which provided a map of coastal wetland vulnerability. Then we explored the main drivers associated with the vulnerability of each coastal wetland by performing a Principal Components Analysis with Agglomerative Hierarchical Clustering, which allowed us to group coastal wetlands according to the drivers analyzed. We found that 42.6 ± 9.2 % of the coastal wetlands evaluated have high or very high vulnerability, with higher vulnerability at the 500 m scale (51.4 %). We identified four groups of coastal wetlands: two located in central Chile, mainly affected by climate change-associated drivers (41.9 ± 2.1 %), and one in central Chile which is affected by land cover change (52.8 ± 6.2 %); the latter has a lower vulnerability level. The most vulnerable coastal wetlands were located in central Chile. Our results present novel findings about the current vulnerability of coastal wetlands, which could be validated by governmental institutions in field campaigns. Finally, we believe that our methodological approach could be useful to generate similar assessments in other world zones. © 2023 Elsevier B.V.